Kandungan Gizi dan Uji Organoleptik Formula Enteral Tepung Growol dan Kecambah Kacang Hijau sebagai Alternatif Enteral Diabetes Melitus Tipe 2: Nutritional and Organoleptic Value in the Formula Enteral of Growol and Germinated Mung Bean Flour as an Alternative Enteral Type 2 Diabetes Mellitus - Nurrohima, Diana; Rahman, Nur; Luthfiyah, Fifi (Amerta Nutrition, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic disease characterized by increased blood glucose. Nutritional support rich in dietary fiber and high protein can stimulate insulin secretion, thereby inhibiting increased blood glucose. Enteral of Growol-Germinated Mung Bean Flour (ENGROCAJO) is a formula developed from growol flour and germinated mung bean flour. It contains high dietary fiber with protein and is an alternative nutritional therapy for people with T2DM. Hospital Diabetes Mellitus (DM) enteral formula administered to patients is limited to dietary fiber. Objectives: This study aimed to analyze the nutritional value and organoleptic value of the ENGROCAJO formula and compare it with the hospital DM enteral formula. Methods: This was an observational laboratory study developed an enteral formula from growol and germinated mung bean flour. It analyzed the nutritional value using proximate and dietary fiber analysis. The organoleptic assessment utilized a hedonic test with 20 participants. The nutritional and organoleptic contents were compared with hospital DM enteral formula. The difference test between formulas was tested using Kruskal-Wallis with a significant value of p<0.05. Results: The nutritional content in 100 g of ENGROCAJO formula and hospital DM enteral formula includes energy of 386.86 and 329.49 kcal, protein of 41.38% and 20.43%, fat of 2.78% and 8.88%, carbohydrate of 49.08% and 38.55% with dietary fiber of 22.43% and 3.62%. Organoleptic assessment of aroma, color, flavor, and thickness showed that the ENGROCAJO formula had higher quality than the hospital DM enteral formula. However, the flavor aspect showed significant difference (p=0.038). Conclusions: ENGROCAJO formula contains higher protein and dietary fiber compared to the hospital DM enteral formula. There was a significant difference in the organoleptic taste between the ENGROCAJO formula and the hospital DM enteral formula.